CSWS Versus SIADH as the Probable Causes of Hyponatremia in Children With Acute CNS Disorders - SORKHI, Hadi; SALEIOMRAN, MohammadReza; BARARI SAVADKOHI, Rahim; BAGHDADI, Farkhondeh; NAKHJAVANI, Naeemeh; BIJANI, Ali (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Sorkhi H, Salehi Omran MR, Barari Savadkoohi R, Baghdadi F, Nakhjavani N, Bijani A. CSWS versus SIADH as the probable Causes of Hyponatremia in Children with Acute CNS Disorders. Iran J Child Neurol. 2013 Summer;7(3): 34-39. Objective There is a major problem about the incidence, diagnosis, and differentiation of cerebral salt wasting syndrome (CSWS) and syndrome of inappropriate secretion of antidiuretic hormone (SIADH) in patients with acute central nervous system (CNS) disorders. According to rare reports of these cases, this study was performed in children with acute CNS disorders for diagnosis of CSWS versus SIADH. Materials & Methods This prospective study was done on children with acute CNS disorders. The definition of CSWS was hyponatremia (serum sodium ≤130 mEq/L), urine volume output ≥3 ml/kg/hr, urine specific gravity ≥1020 and urinary sodium concentration ≥100 mEq/L. Also, patients with hyponatremia (serum sodium ≤130 mEq/L), urine output < 3 ml/kg/hr, urine specific gravity ≥1020, and urinary sodium concentration >20 mEq/L were considered to have SIADH. Results Out of 102 patients with acute CNS disorders, 62 (60.8%) children were male with mean age of 60.47±42.39 months. Among nine children with hyponatremia (serum sodium ≥130 mEq/L), 4 children had CSWS and 3 patients had SIADH. In 2 cases, the cause of hyponatremia was not determined. The mean day of hyponatremia after admission was 5.11±3.31 days. It was 5.25±2.75 and 5.66± 7.23 days in children with CSWS and SIADH, respectively. Also, the urine sodium (mEq/L) was 190.5±73.3 and 58.7±43.8 in patients with CSWS and SIADH, respectively. Conclusion According to the results of this study, the incidence of CSWS was more than SIADH in children with acute CNS disorders. So, more attention is needed to differentiate CSWS versus SIADH in order to their different management. References 1. Peters JP, Welt LG, Sims EAH. A salt wasting syndrome associated with cerebral disease. Trans Assoc Am Physiciants 1957;63:57-64. 2. Schwartz WB, Bennett W, Curelop S. A syndrome of renal sodium loss and hyponatremia probably resulting from inappropriate secretion of antiduretic hormone. Am J Med 1950:23(4); 529-42. 3. Hasan D, Wijdicks EF, Vermeulen M. Hyponatremia is associated with cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage. Ann Neurol 1990;27(1):106-8. 4. Sherlock M, O’Sullivan E, Agha A, Behan LA, Rawluk D, Brennan P, et al. The incidence and pathophysiology of hyponatraemia after subarachnoid haemorrhage. Clin Endocrinol (Oxf). 2006;64(3):250-4. 5. Wartenberg KE, Schmidt JM, Claassen J, Temes RE, Frontera JA, Ostapkovich N, et al. Impact of medical complications on outcome after subarachnoid hemorrhage. Crit Care Med 2006;34(3):617-23; quiz 624. 6. Qureshi AI, Suri MF, Sung GY, Straw RN, Yahia AM, Saad M, et al. Prognostic significance of hypernatremia and hyponatremia among patients with aneurysmal subarachnoid hemorrhage. Neurosurgery 2002;50(4):749-55. 7. Bianchetti MG, Simonetti GD, Bettinelli A. Body fluids and salt metabolism - Part I. Ital J Pediatr 200919;35(1):36. 8. Peruzzo M, Milani GP, Garzoni L, Longoni L, Simonetti GD, Bettinelli A, et al. Body fluids and salt metabolism - part II. Ital J Pediatr 2010;36(1):78. 9. Moritz ML, Ayus JC. New aspects in the pathogenesis, prevention, and treatment of hyponatremic encephalopathy in children. Pediatr Nephrol. 2010;25(7):1225-38. 10. Albanese A, Hindmarsh P, Stanhope R. Management of hyponatraemia in patients with acute cerebral insults. Arch Dis Child 2001;85(3):246-51. 11. Brimioulle S, Orellana-Jimenez C, Aminian A, Vincent JL. Hyponatremia in neurological patients: cerebral salt wasting versus inappropriate antidiuretic hormone secretion. Intensive Care Med 2008;34(1):125-31. 12. Yee AH, Burns JD, Wijdicks EF. Cerebral salt wasting: pathophysiology, diagnosis, and treatment. Neurosurg Clin N Am 2010;21(2):339-52. 13. Palmer BF. Hyponatraemia in a neurosurgical patient: syndrome of inappropriate antidiuretic hormone secretion versus cerebral salt wasting. Nephrol Dial Transplant 2000;15(2):262-8. 14. Rivkees SA. Differentiation appropriate antiduretic hormone secretion, inappropriate antiduretic secretion and cerebral salt wasting: the common, uncommon, and misnamed. Curr Opin Pediatr 2008;20(4):448-52. 15. Sterns RH, Silver SM. Cerebral salt wasting versus SIADH: What difference? J Am Soc Nephrol 2008;19(2):194-6. 16. Jiménez R, Casado-Flores J, Nieto M, García-Teresa MA. Cerebral salt wasting syndrome in children with acute central nervous system injury. Pediatr Neurol 2006;35(4):261-3. 17. Bartter FC, Schwartz WB. Syndrome of inappropriate secretion of antidiuretic hormone. Am J Med 1967;42:790- 806. 18. Verbalis JG. Pathogenesis of hyponatremia in an experimental model of the syndrome of inappropriate antidiuresis. Am J Physiol 1994;267(6 Pt 2):R1617-25. 19. Harrigan MR. Cerebral salt wasting syndrome: a review. Neurosurgery 1996;38(1):152-60. 20. Inatomi J, Yokoyama Y, Sekine T, Igarashi T. A case of cerebral salt-wasting syndrome associated with aseptic meningitis in an 8-year-old boy. Pediatr Nephrol 2008;23(4):659-62. 21. Brookes MJ, Gould TH. Cerebral salt wasting syndrome in meningoencephalitis: a case report. J Neurol Neurosurg Psychiatry 2003;74(2):277. 22. Cuardrado-Godia E, Cerda M, Rodriguez-Campello A, Puig de Dou J. Sindrome pierde sal cerebral en las infeccioned del sistema nervioso central. Med Clin (Barc) 2007;24:128(7);229-9. 23. Roca-Ribas F, Ninno JE, Gasperin A, Lucas M, Liubia C. Cerebral salt wasting syndrome as a postoperative complication after surgical resection of acoustic neuroma. Otol Neurotol 2002;23:992-5. 24. Bussmann C, Bast T, Rating D. Hyponatraemia in children with acute CNS disease: SIADH or cerebral salt wasting? Childs Nerv Syst 2001;17(1-2):58-62. 25. Hardesty DA, Kilbaugh TJ, Storm PB. Cerebral Salt Wasting Syndrome in Post-Operative Pediatric Brain Tumor Patients. Neurocrit Care 2012;17(3):382-7. 26. Agha A, Thornton E, O’Kelly P, Tormey W, Phillips J, Thompson CJ. Posterior pituitary dysfunction after traumatic brain injury. J Clin Endocrinol Metab 2004;89(12):5987-92. 27. Singh S, Bohn D, Carlotti AP, Cusimano M, Rutka JT, Halperin ML. Cerebral salt wasting: truths, fallacies, theories, and challenges. Crit Care Med. 2002 Nov;30(11):2575-9. 28. Carlotti AP, Bohn D, Rutka JT, Singh S, Berry WA, Sharman A, et al. A method to estimate urinary electrolyte excretion in patients at risk for developing cerebral salt wasting. J Neurosurg 2001;95(3):420-4. 29. International committee for Standardization in Haematology. Recommended methods for measurement of red-cell and plasma volume. J Nucl Med 1980:21(8);793-800. 30. Byeon JH, Yoo G. Cerebral salt wasting syndrome after calvarial remodeling in craniosynostosis. J Korean Med Sci 2005;20(5):866–9. 31. Gutierrez OM, Lin HY. Refractory hyponatremia. Kidney Int 2007; 71(1):79-82. 32. Maesaka JK, Imbriano LJ, Ali NM, Ilamathi E. Is it cerebral or renal salt wasting? Kidney Int 2009; 76(9):934-8. 33. Maesaka JK, Venkatesan J, Piccione JM, Decker R, Dreisbach AW, Wetherington JD. Abnormal urate transport in patients with intracranial disease. Am J Kidney Dis 1992;19(1):10-5. 34. Berendes E, Walter M, Cullen P, Prien T, Van Aken H, Horsthemke J, et al. Secretion of brain natriuretic peptide in patients with aneurysmal subarachnoid haemorrhage. Lancet 1997 Jan 25;349(9047):245-9. 35. Kurokawa Y, Uede T, Ishiguro M, Honda O, Honmou O, Kato T, et al. Pathogenesis of hyponatremia following subarachnoid hemorrhage due to ruptured cerebral aneurysm. Surg Neurol 1996;46(5):500-7. 36. Khurana VG, Wijdicks EF, Heublein DM, McClelland RL, Meyer FB, Piepgras DG, et al. A pilot study of dendroaspis natriuretic peptide in aneurysmal subarachnoid hemorrhage. Neurosurgery 2004;55(1):69- 75. 37. Kaneko T, Shirakami G, Nakao K, Nagata I, Nakagawa O, Hama N, et al. C-type natriuretic peptide (CNP) is the major natriuretic peptide in human cerebrospinal fluid. Brain Res 1993;612(1-2):104-9. 38. Damaraju SC, Rajshekhar V, Chandy MJ. Validation study of a central venous pressure-based protocol for the management of neurosurgical patients with hyponatremia and natriuresis. Neurosurgery 1997;40(2):312-6. 39. Sivakumar V, Rajshekhar V, Chandy MJ. Management of neurosurgical patients with hyponatremia and natriuresis. Neurosurgery 1994;34(2):269-74; discussion 274.